Target Specific 51.0 m Long Wing Semi-pelagic Trawl for Off-bottom fishing in Indian EEZ - V., Vijayan; R.S., Manoharadoss; Cubelio, Sherine Sonia (Fishery Technology, 2025)
Target specific 51.0 m long wing semi-pelagic trawl developed for optimum exploitation of off-bottom resources in the Indian EEZ was tested onboard FORV Sagar Sampada in combination with 1.5 t ’V form otter board and 50.0 m double bridles in the depth range of 43.0 to 68.0 m employing three different speeds of tow. The area of experimentation extended between 20Â° 39’ to 21Â° 37’ N Latitude and 69Â° 11’ to 70Â° 16’ E Longitude. Design details of the trawl along with rigging particulars of the gear system are described. A total yield of 3.65 t was realized from 24 hauls made and the average and maximum catch per unit effort amounted to 123.6 and 151.0 kg respectively. 4.0 knot trawling speed was assessed to be the optimum for this gear system. Semipelagic species consisting mainly of Tachysurus sp., Sphyraena sp., Trichiurus sp., Priacanthus hamrur, Megalaspia cordyla, Protonibea diacanthus, Nemipterus japonicus, Polynemus indicus, Saurida tumbil, Scomberomorus sp., Chirocentrus sp., Chorinemus tol, Pseudocaranx dentex, squid and cuttlefish and miscellaneous off-bottom fish constituted over 85% of the total catch, establishing the target specificity of the gear system in landing semi-pelagic fishery resources.